Postnatal care service utilization and its determinants in East Gojjam Zone, Northwest Ethiopia: A mixed-method study. - Liknaw Bewket Zeleke (Public Library of Science (PLoS), 2021)
Background The days and weeks after childbirth are crucial for both the mother and her newborn child leading for the majority of maternal and perinatal mortalities. The World Health Organization recommends at least three postnatal visits within 42 days after birth. However, postnatal care utilization remains low worldwide. Quantitative findings revealed low utilization of postnatal care in Ethiopia, however, no study explored the barriers for postnatal care. This study aimed to assess the barriers to postnatal care service utilization in East Gojjam Zone, Northwest Ethiopia. Methods A community-based, mixed type cross-sectional study was conducted from December 15, 2018, to February 15, 2019. The quantitative data was gathered using the interviewer-administered interviewing technique from 751 women who gave birth within one year prior to the study selected by multistage sampling. The qualitative data were collected from purposively sampled women, facility leaders, and health extension workers using in-depth interviews and focused group discussions. The quantitative and qualitative data were analyzed using logistic regression and by the thematic content analysis method, respectively. Results The study revealed that postnatal care service utilization was 34.6%. The odds of using PNC services were greater in women aged 25-34 years and used maternity waiting home. In contrast, women who were muslim religion followers, had normal or instrumental birth, not aware of the PNC services and whose partners were not supportive of the use of MCH services were less likely to use PNC services. According to the qualitative findings, lack of awareness, traditional beliefs and religious practices, distance and transportation, environmental exposure, and waiting time were identified as barriers to PNC service utilization. Conclusion and recommendation The study showed low utilization of PNC services in East Gojjam zone, northwest Ethiopia. Improvements in personal health education, in construction of relevant infrastructure, and to transport, are needed to remove or reduce barriers to PNC service use in East Gojjam Zone, Northwest Ethiopia.